2011
DOI: 10.1007/s11121-011-0222-9
|View full text |Cite
|
Sign up to set email alerts
|

Food Insufficiency and Medication Adherence Among People Living with HIV/AIDS in Urban and Peri-Urban Settings

Abstract: Food insufficiency is associated with medication non-adherence among people living with HIV/AIDS. The current study examines the relationship between hunger and medication adherence in a US urban and peri-urban sample of people living with HIV/AIDS. Men (N=133) and women (N=46) living with HIV/AIDS were recruited using snowball sampling and small media in Atlanta, Georgia. Participants completed computerized behavioral interviews that included measures of demographics, food insufficiency, social support, depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…We were aware of two additional papers meeting inclusion criteria [37,38] from a previous review on food insecurity and ART adherence [39] that were not identified through the database search. Two papers on food insecurity and ART adherence were from the same study [40,41] presenting measures of association from overlapping samples of PLHIV, and both were included. Two additional papers were on sub-samples from a large survey population in Cameroon and both were included [42,43].…”
Section: Food Insecurity and Art Adherencementioning
confidence: 99%
See 4 more Smart Citations
“…We were aware of two additional papers meeting inclusion criteria [37,38] from a previous review on food insecurity and ART adherence [39] that were not identified through the database search. Two papers on food insecurity and ART adherence were from the same study [40,41] presenting measures of association from overlapping samples of PLHIV, and both were included. Two additional papers were on sub-samples from a large survey population in Cameroon and both were included [42,43].…”
Section: Food Insecurity and Art Adherencementioning
confidence: 99%
“…Twelve studies [13,37,38,[40][41][42][43][45][46][47][48][49] were cross-sectional, five were prospective cohort studies [15,16,[50][51][52], one was a retrospective cohort [53], and one was a case-control study [54]. One cross-sectional study [37] analyzed ART adherence as the exposure and food insecurity as the outcome (the inverse of the pathway of interest); this study is included but cannot be directly compared to the other studies that examined food insecurity as the exposure of interest.…”
Section: Characteristics Of Food Insecurity Studiesmentioning
confidence: 99%
See 3 more Smart Citations